Factors influencing hesitancy towards adult and child COVID-19 vaccines in rural and urban West Africa: a cross-sectional study. Issue 4 (13th April 2022) - Faye, Sylvain Landry B.; Krumkamp, Ralf; Doumbia, Seydou; Tounkara, Moctar; Strauss, Ricardo; Ouedraogo, Henri Gautier; Sagna, Tani; Barry, Alpha Mahmoud; Mbawah, Abdul Karim; Doumbia, Cheick Oumar; Diouf, Souleymane; Cisse, Kadari; et al.
Abstract : Objectives: This study aims: (1) to identify and describe similarities and differences in both adult and child COVID-19 vaccine hesitancy, and (2) to examine sociodemographic, perception-related and behavioural factors influencing vaccine hesitancy across five West African countries. Design: Cross-sectional survey carried out between 5 May and 5 June 2021. Participants and setting: 4198 individuals from urban and rural settings in Burkina Faso, Guinea, Mali, Senegal and Sierra Leone participated in the survey. Study registration: The general protocol is registered on clinicaltrial.gov. Results: Findings show that in West Africa at the time only 53% of all study participants reported to be aware of COVID-19 vaccines, and television (60%, n=1345), radio (56%; n=1258), social media (34%; n=764) and family/friends/neighbours (28%; n=634) being the most important sources of information about COVID-19 vaccines. Adult COVID-19 vaccine acceptance ranges from 60% in Guinea and 50% in Sierra Leone to 11% in Senegal. This is largely congruent with acceptance levels of COVID-19 vaccinations for children. Multivariable regression analysis shows that perceived effectiveness and safety of COVID-19 vaccines increased the willingness to get vaccinated. However, sociodemographic factors, such as sex, rural/urban residence, educational attainment and household composition (living with children and/or elderly), and the other perception parameters were not associated with the willingness to get vaccinated in the multivariable regression model. Conclusions: Primary sources of information about COVID-19 vaccines include television, radio and social media. Communication strategies addressed at the adult population using mass and social media, which emphasise COVID-19 vaccine effectiveness and safety, could encourage greater acceptance also of COVID-19 child vaccinations in sub-Saharan countries. Trial registration number: NCT04912284 .